Novel bioengineered MBenes for the treatment of Alzheimer's disease: An in-Sillico study. Issue 22 (12th December 2022) - Dahri, Mohammad; Miri Jahromi, Ahmad; Nikzad, Arash; Mohammadgholian, Maryam; Rahmanian, Mohammad; Abolmaali, Samira Sadat; Maleki, Reza
Abstract: Alzheimer's disease is a neurodegenerative disease caused by the deposition and accumulation of amyloid-β (Aβ) peptides in the brain neurons. Current medications are not a definitive cure for this disease, but they can hamper the signs and symptoms of Alzheimer's disease. Therefore, prevention is the best way to deal with this disease. In this study, the novel structures based on MBenes (such as Cd2 B, Mo2 B, Cu2 B, and Ta2 B) are proposed to prevent amyloid-β accumulation in Alzheimer's disease. Regarding the remarkable MBene properties such as tunability, biocompatibility, and low manufacturing cost, the effect of these structures on amyloid-β deformation was explored using molecular dynamics simulation. To provide an atomic analysis of Beta-amyloid behavior in the presence of these structures, the compaction, contact area, and stability of Beta-amyloid were investigated. The results indicated the satisfactory performance of MBenes on the destabilization of amyloid-β structures. Moreover, given the higher interactions between Cd2 B and amyloid-β, the instability, compaction, and the contact area of amyloid-β particles were investigated in this complex. The findings confirmed Cd2 B as the best structure to prevent amyloid-β accumulation. The results of this investigation paved the way for the development of these structures as a medicinal agent to prevent Alzheimer's disease. Abstract : UF0001 Communicated by Ramaswamy H. Sarma